HİSSEDAR AKTİVİZMASI VE MALEZYA'DA KURUMSAL SOSYAL SORUMLULUK - ACTIVISM AND CORPORATE SOCIAL RESPONSIBILITY IN MALAYSIA - Muhammad Aiman Awalluddin (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
The purpose of this paper is to shed light on the issues of shareholder activism in Malaysia. The findings shows that shareholder activism already taken place in Malaysia. Although, it is not as rigorously and actively as compare to developed country, the existence of shareholder activism in Malaysia indicated the awareness is rising. Shareholder activism is one of the vital element in corporate governance framework to ensure good governance practice. By engaging company, shareholders ensuring there is a check and balance on the course of action taken by company. Furthermore, the research outcome also indicates shareholders are likely to use voting rights and dialogue in engaging companies to practice good CSR. Voting rights is considered as powerful means because voted resolution shows the will of the shareholder. Additionally, dialogue can enhance transparency and openness between shareholders and management of company. Besides, through dialogue, shareholders may signal to the management of the company on the importance of CSR, instead of shareholder supremacy. Having two way communication can improve mutual understanding between both parties and indicate good corporate governance.